INVENTARISASI DAN PENGENDALIAN PENYAKIT PARASIT PADA INDUK IKAN LAUT DI BAK PEMELIHARAAN - Bejo Slamet; Tridjoko Tridjoko; Agus P.; T. Setiadharma; N. A. Giri; K. Suwirya (Jurnal Perikanan Universitas Gadjah Mada, 2008)
Observation on parasitic diseases had been conducted in Gondol Research Institute for Marine culture on mild fish (Chanos chanos), seabass (Lates calcarifer), tiger grouper (Epinephelus fuscoguttatus), humpback grouper (Cromileptes altivelis), mangrove grouper (E. coioides), camouflage grouper (E. microdon), coral trout (Plectropoma leopardus, P. maculatus), snappers (Lutjanus argentimaculatus, L. seabae) and napoleon wrasse (Cheilinus undulatus) rearing in captivity. The result showed that Cryptocaryon irritans was found on napoleon wrasse and humpback grouper; Amyloodinium ocellatum was found only on napoleon wrasse; Gill flukes (Haliothrema sp. dan Diplectanum sp. ) was found on humpback grouper and mangrove grouper; skin flukes Neobenedenia sp. was found only on napoleon wrasse and Benedenia was found on all grouper, snapper and seabass; Crustacea (Rhexanella sp.) and copepod (Caligus sp. and Lepeophtheirus sp.) was found on all grouper, snapper and seabass; Hirudinae (Zeylanicobdella arugamensis ) was found on all grouper, snapper and seabass.